Heat storage unit, assembly method thereof and heat pump system
By using phase change materials containing phase change substrates, nucleating agents and corrosion inhibitors in the heat pump system, a protective film is formed to prevent corrosion of metal heat exchange structures, which solves the corrosion problem of phase change materials on the metal structure and improves the reliability of the system and thermal efficiency.
Patent Information
- Application Number
- CN202411364709.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The corrosion problem of phase change materials with metal heat exchange structures in heat pump systems has not been effectively solved, resulting in reduced system reliability and shortened service life.
Using a phase change material including a phase change substrate, a nucleating agent and a corrosion inhibitor, the corrosion inhibitor is combined with metal ions to form a complex to form a protective film to prevent corrosion, and the phase change material is filled with the metal heat storage shell. In the heat storage space, contact the heat exchange tube and thermal conduction fins to achieve corrosion protection.
It effectively prevents corrosion of the metal heat exchange structure, improves the reliability and service life of the system, reduces costs, and improves the thermal energy efficiency of the heat pump system.
Smart Images

Figure CN119245410A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of energy storage materials, and in particular to a heat storage unit and an assembly method and application thereof. Background Art
[0002] With the deepening of industrialization, the energy gap is becoming more and more obvious. The shortage of primary energy has attracted great attention from people. For this reason, humans have come up with many solutions. Improving energy utilization and developing renewable energy have become important issues.
[0003] Phase change energy storage is a technology that uses phase change materials to undergo phase changes (solid-liquid, gas-liquid) for phase change energy storage. The heating process involves two processes: sensible heat storage and latent heat storage. During the latent heat storage process, the material temperature is almost constant. Compared with water that only uses sensible heat to store heat, phase change materials have higher heat storage capacity. Therefore, phase change materials have very high application advantages in heat pump systems. For example, in the temperature range of 10°C to 65°C, the energy storage density of phase change materials can reach twice that of water, and the volume of the phase change module can be reduced to 50% of that of an independent water tank. In the heat pump system, the phase change material absorbs heat from the heat source during its energy storage process, and the phase change material transfers heat to low-temperature domestic water during its heat release process to achieve instant hot water. The higher the phase change temperature of the phase change material, the higher the outlet water temperature.
[0004] In the process of heat storage and release, the phase change material needs to contact the heat exchange structure. So far, the anti-corrosion of phase change materials has been less studied and there is a lack of systematic solutions. In addition, the heat exchange structure is usually made of metal, which is easily corroded. Therefore, the corrosion problem of phase change materials on metal heat exchange structures cannot be ignored. Summary of the invention
[0005] The embodiments of the present application provide a heat storage unit and an assembly method and application thereof, which can solve the problem that phase change materials easily cause corrosion of heat exchange structures made of metal materials.
[0006] In a first aspect, an embodiment of the present application provides a heat storage unit for a heat pump system, wherein the heat storage unit comprises a metal heat storage shell and a phase change layer, wherein the metal heat storage shell has a heat storage space inside, and the phase change layer is filled in the heat storage space;
[0007] Wherein, the phase change layer comprises a phase change material, and the phase change material comprises the following components:
[0008] Phase change substrate 85.0wt.%~95.0wt.%, nucleating agent 1.0wt.%~3.0wt.%, thickener 2.0wt.%~4.0wt.%, corrosion inhibitor 0.5wt.%~2.0wt.%;
[0009] The phase change substrate includes one of saturated fatty acids, alcohol compounds or inorganic phase change substrates;
[0010] The nucleating agent is selected from at least one of phosphates, silicates, and carbonates;
[0011] The corrosion inhibitor includes at least one of nitrogen-containing heterocyclic compounds, oxygen-containing heterocyclic compounds, molybdates, chromates and tungstates.
[0012] In some embodiments, the phase change material comprises the following components based on the total weight of the phase change material:
[0013] Phase change substrate 92wt.%~94wt.%, nucleating agent 2.0wt.%~3.0wt.%, thickener 3.0wt.%~4.0wt.%, corrosion inhibitor 0.5wt.%~1.5wt.%.
[0014] In some embodiments, the weight ratio of the phase change substrate to the corrosion inhibitor ranges from 90.5 to 92.5.
[0015] In some embodiments, the saturated fatty acid of the phase change substrate is selected from at least one of myristic acid, palmitic acid, and fatty acid;
[0016] The alcohol compound of the phase change substrate is selected from at least one of mannitol, polyethylene glycol, and dodecanol;
[0017] The inorganic phase change substrate of the phase change substrate is selected from at least one of sodium sulfate decahydrate, calcium chloride hexahydrate, sodium acetate trihydrate, magnesium chloride hexahydrate, sodium carbonate decahydrate, and sodium thiosulfate pentahydrate.
[0018] In some embodiments, the nitrogen-containing heterocyclic compound of the corrosion inhibitor is selected from at least one of carboxyethyl imidazoline and its derivatives, benzotriazole and its derivatives, and imidazoline;
[0019] The oxygen-containing heterocyclic compound of the corrosion inhibitor is selected from at least one of chitosan-o-vanillin Schiff base, furfural-adenine Schiff base, and furfural-melamine Schiff base;
[0020] The molybdate of the corrosion inhibitor is selected from at least one of sodium molybdate, strontium molybdate and nickel molybdate;
[0021] The chromate of the corrosion inhibitor is selected from at least one of sodium chromate, potassium chromate and magnesium chromate;
[0022] The tungstate of the corrosion inhibitor is selected from at least one of calcium tungstate, sodium tungstate, cobalt tungstate and ferrous tungstate.
[0023] In some embodiments, the thickener is selected from at least one of hydroxymethyl cellulose, soluble starch, gelatin, polyvinyl pyrrolidone, sodium polyacrylate and xanthan gum.
[0024] In some embodiments, the metal thermal storage housing comprises:
[0025] main housing;
[0026] A plurality of heat-conducting fins are arranged in the inner space of the main housing, each of the heat-conducting fins having a heat-conducting hole;
[0027] A heat exchange tube is arranged in the inner space of the main shell and is provided with a plurality of heat conduction holes of the heat conduction fins. The main shell, the plurality of heat conduction fins and the heat exchange tube define the heat storage space;
[0028] The phase change layer is filled in the heat storage space and is in contact with the outer surface of the heat exchange tube and the outer surface of the heat conductive fin to exchange heat with the heat exchange medium in the heat exchange tube;
[0029] A material of at least one of the main housing, the heat conducting fins, and the heat exchange tubes includes copper.
[0030] In a second aspect, the present application provides an assembly method of a heat storage unit, comprising: mixing the components of the phase change material as described above to obtain a final mixture, filling the final mixture into the heat storage space of the metal heat storage shell, and the final mixture forming the phase change layer.
[0031] In some embodiments, mixing the components of the phase change material comprises the following steps:
[0032] The phase change substrate and the corrosion inhibitor are mixed and heated to a preset temperature for emulsification treatment, wherein the preset temperature is greater than the melting point of the phase change substrate to obtain a molten mixture A;
[0033] Mixing the molten mixture A with the nucleating agent to perform a first mixing process to obtain a mixture B;
[0034] Mixing the mixture B with the thickener, and performing a second mixing process to obtain the molten final mixture;
[0035] Filling the heat storage space of the metal heat storage shell with the final mixture includes: filling the heat storage space inside the metal heat storage shell with the molten final mixture, and the molten final mixture is cooled and solidified to form the phase change layer.
[0036] In some embodiments, the emulsification treatment at least includes: the preset temperature is 70°C to 80°C, the stirring speed is 2000r / min to 3000r / min, and the time is 15min to 30min.
[0037] The first mixing process at least includes: a stirring speed of 80 r / min to 120 r / min and a time of 1 h to 2 h;
[0038] The second mixing process at least includes: adding the thickener to the mixture B in batches, with a stirring speed of 20r / min to 40r / min for 2h to 3h, and the weight of the thickener added each time is 20% to 25% of the total weight of the thickener.
[0039] In a third aspect, the present application provides a heat pump system, comprising:
[0040] A heat source, used to provide heat; and
[0041] As described above, the phase change material of the heat storage unit is used to obtain the heat provided by the heat source to perform phase change energy storage.
[0042] Based on the thermal storage unit and its assembly method and application of the embodiment of the present application, by selecting the phase change substrate and the corrosion inhibitor for use in combination, the phase change substrate can provide a solvent for the corrosion inhibitor, promote the dissociation of the corrosion inhibitor and form a negatively charged BTA - 、MnO4 2- 、CrO4 2- At the same time, since the metal of the metal shell will lose electrons when in contact with the phase change material, positively charged metal ions will dissolve in the phase change material. The positively charged metal ions can react with the negatively charged BTA. - 、MnO4 2- 、CrO4 2- The phase change material is alkaline, and in an alkaline environment, it can further promote the forward reaction of the corrosion inhibitor selected in the application in the phase change material, thereby generating negatively charged substances and promoting the formation of complexes on the wall of the metal thermal storage shell. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0044] Figure 1 This is a schematic structural diagram of a heat pump system according to an embodiment of the present application;
[0045] Figure 2 This is a flow chart of a method for preparing a phase change material according to an embodiment of the present application;
[0046] Figure 3a The surface morphology of the copper heat exchange tube in contact with the phase change material in Examples 1-6 in a thermal environment;
[0047] Figure 3b This is a surface morphology diagram of the copper heat exchange tube in contact with the phase change material in Comparative Example 1-1 in a thermal environment;
[0048] Figure 4 The corrosion depth diagram of the copper heat exchange tube in contact with the phase change material in Examples 1-6 in a thermal environment;
[0049] Figure 5 The surface morphology of 304 stainless steel in contact with the phase change material in Examples 1-6 in a thermal environment;
[0050] Figure 6 This is a surface morphology diagram of the aluminum plate in contact with the phase change material in Comparative Example 1-1 in a thermal environment.
[0051] Reference numerals:
[0052] 10. Heat pump system;
[0053] 100. thermal storage unit; 110. metal thermal storage shell;
[0054] 200, heat exchange tube; 210, first heat exchange tube; 220, second heat exchange tube;
[0055] 300, heat source; 310, outlet end; 320, inlet end; 400, heating unit;
[0056] 500, reversing valve; 510, first reversing valve; 520, second reversing valve;
[0057] 610. Municipal water source; 620. Domestic water pipe. DETAILED DESCRIPTION
[0058] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0059] It should be noted that, in various aspects of the present application, for the same components in various aspects, the present application only describes one aspect once without repeating the description, which should not be understood by those skilled in the art as a limitation to the present application.
[0060] In the present application, unless otherwise stated, the room temperature or normal temperature refers to 25±2°C.
[0061] In the related art, inorganic hydrated salts are selected as phase change materials. In order to meet the heat exchange requirements, they are often matched with metal heat exchange structures. For example, the metal heat exchange structure includes stainless steel materials such as copper, aluminum, and stainless steel. Inorganic hydrated salts will cause corrosion to the metal heat exchange structure. Moreover, the amount of inorganic hydrated salts is usually large, which will further aggravate the corrosion of the metal heat exchange structure, reduce product reliability, and greatly shorten the service life of the product. Metal corrosion often appears in the form of electrochemical corrosion, galvanic corrosion, intergranular corrosion, pitting corrosion, uniform corrosion, etc. The inventors have found that by adding corrosion inhibitors to the phase change material system, increasing the thickness of the metal heat exchange structure, etc. to cover the corrosion problem of the entire life cycle, and by coating corrosion-resistant coatings or plating to prevent the corrosion of the metal heat exchange structure by the phase change material, the problem of corrosion of the metal shell can be improved. However, the method of adding corrosion inhibitors needs to be added according to the type of metal. Furthermore, by increasing the thickness of the metal heat exchange structure, the system cost will increase. Finally, the coating or plating method generally has the problem of incomplete coating. Due to the process and the large number of gaps in the metal heat exchange structure, defects are prone to occur, which accelerates corrosion, and the cost will also be high. Based on this, the embodiment of the present application provides a heat storage unit that can improve the corrosion of the metal heat exchange structure by the phase change material.
[0062] The heat storage unit provided in the embodiment of the present application is used in a heat pump system. The heat storage unit includes a metal heat storage shell and a phase change layer. The metal heat storage shell has a heat storage space inside. The phase change layer fills the heat storage space. The phase change layer includes a phase change material. The phase change material is used to exchange heat with the material in the heat storage space to perform phase change energy storage.
[0063] The phase change material of the embodiment of the present application includes the following components:
[0064] Phase change substrate 85.0wt.%~95.0wt.%, nucleating agent 1.0wt.%~3.0wt.%, thickener 2.0wt.%~4.0wt.%, corrosion inhibitor 0.5wt.%~2.0wt.%, the phase change substrate includes at least one of saturated fatty acids, alcohol compounds and inorganic phase change substrates, and the corrosion inhibitor includes at least one of nitrogen-containing heterocyclic compounds, oxygen-containing heterocyclic compounds, molybdates, chromates and tungstates.
[0065] In the present application, the phase change substrate is the main component of the phase change material that undergoes phase change, and the nucleating agent is used to provide nucleation sites for the phase change substrate so that the phase change material can be repeatedly melted and crystallized, thereby performing phase change energy storage. The thickener is used to increase the overall viscosity of the phase change material. The thickener can capture water molecules and prevent them from escaping, thereby inhibiting the phase separation of the phase change material and making the phase change material have good stability during frequent phase changes.
[0066] The present invention selects a phase change substrate including a saturated fatty acid, an alcohol compound or an inorganic phase change substrate, and the corrosion inhibitor includes at least one of a nitrogen-containing heterocyclic compound, an oxygen-containing heterocyclic compound, a molybdate, a chromate and a tungstate. The phase change substrate can provide a solvent for the corrosion inhibitor, promote the dissociation of the corrosion inhibitor and form a negatively charged BTA. - 、MnO4 2- 、CrO4 2- Substances such as BTA: BTA+OH - =BTA - +H2O), and at the same time, since metal ions will dissolve in the phase change material, it can promote the metal of the metal thermal storage shell to lose electrons (such as iron oxygen absorption corrosion: 2Fe+O2+2H2O==2Fe 2+ +4OH - ), forming positively charged metal ions, positively charged metal ions (e.g., Cu 2+ , Fe 2+ 、Al 3+ ) can react with negatively charged BTA - 、MnO4 2- 、CrO4 2- It combines to form a dense long-chain complex, and forms a protective film on the metal surface by physical adsorption, which inhibits other corrosive ions from further contacting the metal, thereby achieving the purpose of corrosion protection. Among them, the phase change material is alkaline, and in an alkaline environment, it can further promote the forward reaction of the corrosion inhibitor selected in the present application in the phase change material, thereby generating negatively charged substances and promoting the formation of complexes on the wall of the metal thermal storage shell. In the embodiment of the present application, by selecting the components of the phase change substrate, nucleating agent, thickener and corrosion inhibitor within a suitable range, and after the components of the phase change substrate, nucleating agent and thickener are mixed, the entire phase change material system can be made alkaline, which helps to further promote the formation of complexes on the wall of the complex metal thermal storage shell and enhance the anti-corrosion effect.
[0067] In the embodiment of the present application, the components of the phase change material can be mixed evenly, and the phase change material can be heated and molten and filled into the heat storage space, and the phase change layer can be formed after the molten phase change material solidifies. The corrosion inhibitor is evenly dispersed in the phase change layer. During the process of repeated melting and crystallization of the phase change material in the phase change layer, the corrosion inhibitor is evenly in contact with the wall surface of the metal heat storage shell, and a protective film is formed on the wall surface of the metal heat storage shell. Taking the metal heat storage shell comprising copper material and the corrosion inhibitor comprising benzotriazole (BTA) as an example, the anti-corrosion mechanism of the corrosion inhibitor is as follows:
[0068]
[0069] When the phase change material is heated and molten, benzotriazole (BTA) is solvated. Reaction ① is a reversible reaction. When BTA is in an alkaline environment, the concentration of BTA ions will increase to a greater extent. Copper (metal) is oxidized and loses electrons to generate cuprous ions Cu. + (metal ion); Cu + (metal ions) form dense long-chain complexes with BTA ions (corrosion inhibitor ions), and through physical adsorption on the metal surface, inhibit other corrosive ions from further contacting the metal, thereby achieving the purpose of corrosion protection.
[0070] When the weight percentage of the phase change substrate is lower than the lower limit of 85.0wt.%, the content of the phase change substrate decreases, resulting in a lower thermal enthalpy value of the phase change material. When the weight percentage of the phase change substrate is higher than the upper limit of 95.0wt.%, the content of other components of the phase change material except the phase change substrate decreases, and the phase change material has problems such as decreased phase stability and increased supercooling. When the weight percentage of the corrosion inhibitor is lower than the lower limit of 0.5wt.%, due to the low content of the corrosion inhibitor, the coverage and thickness of the surface complex formed are poor, and the metal protection effect is poor. When the weight percentage of the corrosion inhibitor is higher than the upper limit of 1.5wt.%, it will cause redundant corrosion inhibitors, resulting in waste of costs, and will increase the environmental burden.
[0071] In some embodiments, the phase change substrate is 92 wt.% to 94 wt.%, the nucleating agent is 2.0 wt.% to 3.0 wt.%, the thickener is 3.0 wt.% to 4.0 wt.%, and the corrosion inhibitor is 0.5 wt.% to 1.5 wt.%. Under this composition, the components of the phase change material can be dispersed more stably, the phase change stability is better, the water temperature is more stably regulated, and the hot water production efficiency of the heat pump system can be further improved. At the same time, the entire phase change material has less corrosion on the wall of the metal heat storage shell.
[0072] In some embodiments, the weight ratio of the phase change substrate to the corrosion inhibitor is 90.5-92.5. Within this ratio range, the phase change substrate and the corrosion inhibitor cooperate with each other to further improve the corrosion of the metal thermal storage shell wall by the phase change material.
[0073] The melting point Tm of the phase change substrate is the basis of the phase change temperature of the phase change material. In the embodiment of the present application, the phase change temperature of the phase change material is similar to the melting point Tm of the phase change substrate.
[0074] In some embodiments, the saturated fatty acid of the phase change substrate is selected from at least one of myristic acid, myristic acid, and palmitic acid. At this time, the melting point Tm of the saturated fatty acid ranges from 25°C to 60°C. By selecting the above-mentioned saturated fatty acids, molybdate, chromate and tungstate corrosion inhibitors can promote the formation of molybdate, chromate and tungstate in an acidic environment, and can quickly passivate the corroded metal and form a dense oxide film on the surface to achieve an anti-corrosion effect.
[0075] In some embodiments, the alcohol compound of the phase change substrate is selected from at least one of mannitol, polyethylene glycol, and dodecanol. At this time, the melting point Tm of the alcohol compound ranges from 20°C to 65°C. By selecting the above-mentioned alcohol compounds, the solubility of nitrogen-containing heterocyclic compounds, oxygen-containing heterocyclic compounds and polar corrosion inhibitors can be greatly improved, so that the solvation degree of such corrosion inhibitors is increased to achieve better uniformity of corrosion inhibitor dispersion.
[0076] In some embodiments, the inorganic phase change substrate of the phase change substrate is selected from at least one of sodium sulfate decahydrate, calcium chloride hexahydrate, sodium acetate trihydrate, magnesium chloride hexahydrate, sodium carbonate decahydrate, and sodium thiosulfate pentahydrate. At this time, the melting point Tm range of the inorganic phase change substrate is 30°C to 60°C. By selecting the above-mentioned inorganic phase change substrate, this type of inorganic salt belongs to a strong base and weak acid or a strong base and strong acid salt (a weakly alkaline or neutral hydrated salt). Since the alkaline environment is full of OH - ions, thus effectively promoting the formation of anions and achieving the effect of quickly forming a dense complex with metal cations.
[0077] In some embodiments, the nitrogen-containing heterocyclic compound of the corrosion inhibitor is selected from at least one of carboxyethyl imidazoline and its derivatives, benzotriazole and its derivatives. The oxygen-containing heterocyclic compound of the corrosion inhibitor is selected from at least one of chitosan-o-vanillin Schiff base, furfural-adenine Schiff base, and furfural-melamine Schiff base. The molybdate of the corrosion inhibitor is selected from at least one of sodium molybdate, strontium molybdate, and nickel molybdate, and the chromate of the corrosion inhibitor is selected from at least one of sodium chromate, potassium chromate, and magnesium chromate. The tungstate of the corrosion inhibitor is selected from at least one of calcium tungstate, sodium tungstate, and cobalt tungstate. By selecting the above-mentioned corrosion inhibitors, it is possible to combine with a variety of metal ions to form complexes when the phase change material system is alkaline, so that the material of the metal thermal storage shell can have more choices. The diversity of the choice of corrosion inhibitors means that the mechanism of corrosion inhibition is not only the formation of complexes, but also the compounding of corrosion inhibitors can effectively passivate the metal to achieve the purpose of corrosion protection.
[0078] In some embodiments, the nucleating agent is selected from at least one of phosphate, silicate and carbonate. Among them, the phosphate of the nucleating agent is selected from at least one of sodium dihydrogen phosphate and disodium hydrogen phosphate dodecahydrate, the carbonate of the nucleating agent is selected from at least one of calcium carbonate and magnesium carbonate, and the silicate of the nucleating agent is selected from at least one of sodium metasilicate pentahydrate and calcium silicate. By selecting the above nucleating agent, a crystallization site can be provided for the phase change substrate, so that the phase change material can be repeatedly melted-crystallized, and the phase change stability is better.
[0079] When the nucleating agent is an insoluble particle, the particle size Dv is selected in the embodiment of the present application. 50 Meet 200μm≤Dv 50 Nucleating agent with a particle size of ≤400 μm. Within this particle size range, the nucleating agent can be uniformly dispersed in the phase change material to provide crystallization sites for the phase change material.
[0080] In some embodiments, the thermal conductivity of the phase change substrate is relatively poor, and the phase change material further comprises a thermal conductive filler, which has good thermal conductivity and is used to improve the overall thermal conductivity of the phase change material to improve the heat transfer efficiency of the phase change material. Based on the total weight of the phase change material, the weight percentage of the thermal conductive filler is 1.0wt.% to 7.0wt.%. The thermal conductive filler is selected from at least one of fumed silica, copper foam, expanded graphite, carbon nanotubes and molybdenum disulfide.
[0081] The metal heat storage shell includes a main shell and a plurality of heat-conducting fins, wherein the plurality of heat-conducting fins are arranged in the internal space of the main shell, and a part of the phase change material is filled in the gap between two adjacent heat-conducting fins, and another part is filled in the gap between the heat-conducting fins and the main shell. Among them, the spacing between two adjacent heat-conducting fins is L1, and the spacing between the heat-conducting fins and the inner wall surface of the main shell is L2, 1.3mm≤L1≤1.8mm, 3mm≤L2≤6mm, within this spacing range, the various components of the molten phase change material can smoothly enter the metal heat storage shell, and evenly enter the gap between two adjacent heat-conducting fins and the gap between the heat-conducting fins and the main shell, preventing the generation of bubbles.
[0082] The heat storage unit also includes a heat exchange tube, the heat conduction fin has a heat conduction hole, the heat exchange tube is provided with a plurality of heat conduction holes of the heat conduction fin, and the end of the heat exchange tube extends out of the metal heat storage shell, and the main shell, the plurality of heat conduction fins and the heat exchange tube define a heat storage space. The phase change material is filled in the heat storage space and coated on the outer surface of the heat exchange tube to exchange heat with the heat exchange medium in the heat exchange tube, and is connected to the heat exchange tube through a plurality of heat conduction fins. The heat exchange tube can also exchange heat with the phase change material through the heat conduction fins, thereby increasing the heat exchange area and improving the heat exchange efficiency.
[0083] It is understandable that copper has excellent thermal conductivity, but copper also has the disadvantage of poor corrosion resistance. In the embodiment of the present application, the material of at least one of the main shell, the heat-conducting fins and the heat exchange tubes may include copper. By selecting the type and content of each component of the phase change material, even in the presence of copper material, when the phase change material contacts the copper-containing parts in the main shell, the heat-conducting fins and the heat exchange tubes, the degree of corrosion of the phase change material to the parts is relatively small. The phase change material is filled in the heat storage space, and the corrosion inhibitor is evenly distributed in the entire system of the phase change material, which can also prevent the formation of corrosion dead corners.
[0084] The heat exchange tube includes an inlet section, an intermediate section and an outlet section connected in sequence, the intermediate section is arranged in the heat storage space, and the inlet section and the outlet section extend out of the metal heat storage shell from the heat storage space. The phase change material is filled in the heat storage space and coated on the intermediate section of the heat exchange tube to exchange heat with the heat exchange medium in the heat exchange tube. The heat exchange tube is used to connect with other structures of the heat pump system to transport the heat exchange medium. The number of heat exchange tubes of the heat storage unit can be multiple, so that the heat storage unit can be connected with multiple structural parts of the heat pump system for heat exchange.
[0085] like Figure 1 As shown, it is a structural schematic diagram of a heat pump system 10 of an embodiment of the present application. The heat pump system 10 also includes a heat source 300, which is used to provide heat. The heat source 300 is connected to at least one of the heat exchange tubes 200 of the heat storage unit 100, so that the heat provided by the heat source 300 can be supplied to at least one heat exchange tube 200, and then transferred to the inorganic hydrated phase change material of the phase change layer for heat storage.
[0086] For example, Figure 1In the heat exchange tube 200, there are two, one of which is the first heat exchange tube 210 and the other is the second heat exchange tube 220. The inlet section of the first heat exchange tube 210 is connected to the outlet end 310 of the heat source 300, and the outlet section is connected to the inlet end 320 of the heat source 300. The inlet section of the second heat exchange tube 220 is connected to the municipal water source 610, and the outlet section is connected to the domestic water pipe 620. The heat storage unit 100 has a heat storage mode, a heat release mode and a mixed mode. Specifically, in the heat storage mode, the high-temperature heat exchange medium of the heat source 300 enters the first heat exchange tube 210 from the inlet section of the first heat exchange tube 210, and the phase change material absorbs the heat of the high-temperature heat exchange medium in the first heat exchange tube 210 and stores the heat. The high-temperature heat exchange medium becomes a low-temperature heat exchange medium and flows back from the outlet section of the first heat exchange tube 210 to the inlet end 320 of the heat source 300; in the heat release mode, the low-temperature water flow supplied by the municipal water source 610 flows from the second heat exchange tube 220 to the inlet end 320 of the heat source 300. The inlet section of tube 220 enters the second heat exchange tube 220, and the phase change substrate transfers heat to the low-temperature water flow in the second heat exchange tube 220. The low-temperature water flow absorbs heat and becomes high-temperature water flow, and flows out from the outlet section of the second heat exchange tube 220 for user use; in the mixed mode, the high-temperature heat exchange medium of the heat source 300 enters the first heat exchange tube 210 from the inlet section of the first heat exchange tube 210. At the same time, the low-temperature water flow supplied by the municipal water source 610 enters the second heat exchange tube 220 from the inlet section of the second heat exchange tube 220. The phase change material absorbs the heat of the high-temperature heat exchange medium in the first heat exchange tube 210 and simultaneously transfers the heat to the low-temperature water flow in the second heat exchange tube 220. The low-temperature water flow absorbs heat and becomes high-temperature water flow or medium-temperature water flow, and flows out from the outlet section of the second heat exchange tube 220 for user use.
[0087] The heat pump system 10 also includes a heating unit 400, a reversing valve 500 and connecting pipes connecting the various structures. The reversing valve 500 includes a first reversing valve 510. The first end of the first reversing valve 510 is connected to the outlet end 310 of the heat source 300, the second end is connected to the heating unit 400, and the third end is connected to the heat exchange pipe 200 of the heat storage unit 100. By switching the flow path of the first reversing valve 510, the outlet end 310 of the heat source 300 can be connected to at least one of the heating unit 400 and the heat storage unit 100 to provide high-temperature heat exchange medium to the heating unit 400 and the heat storage unit 100 accordingly. The number of heating units 400 may be multiple, and the reversing valve 500 may also include a second reversing valve 520. The second reversing valve 520 is arranged on the second end of the first reversing valve 510 and is connected to a connecting pipe connected to the multiple heating units 400. By switching the flow path of the second reversing valve 520, the second end of the first reversing valve 510 is connected to one or more of the multiple heating units 400, and then the heat source 300 is connected to one or more of the multiple heating units 400.
[0088] The present application also provides a method for assembling a heat storage unit, such as Figure 2As shown, the assembly method includes:
[0089] Step S1: Mix the components of the phase change material as described above.
[0090] Step S2: Fill the heat storage space inside the metal heat storage housing with the components of the mixed phase change material.
[0091] Figure 2 In [description], step S1 of mixing the components of the phase change material includes the following steps:
[0092] Step S110: Mix the phase change substrate with the corrosion inhibitor, heat it to a preset temperature, and perform emulsification treatment. The preset temperature is greater than the melting point of the phase change substrate to obtain a molten mixture A;
[0093] Step S120: Mix the molten mixture A with the nucleating agent and perform a first mixing treatment to obtain a mixture B;
[0094] Step S130: Mix the mixture B with the thickening agent and perform a second mixing treatment to obtain the final mixture.
[0095] Step S2 includes: filling the heat storage space inside the metal heat storage housing with the molten final mixture obtained in step S130, and the molten final mixture cools and solidifies to form a phase change layer.
[0096] In the embodiments of the present application, after the components of the phase change material are melted and mixed evenly, they can be filled into the heat storage space inside the metal heat storage housing in a molten state. The components mixed together can also be dispersed evenly. When the molten final mixture is filled into the heat storage space inside the metal heat storage housing, the molten final mixture can contact the wall surface of the metal heat storage housing without difference, enabling the corrosion inhibitor to contact the wall surface of the metal heat storage housing, having a good anti-corrosion effect, and moreover, the phase change material has good stability during both the heat storage and heat release processes.
[0097] In some embodiments, the emulsification treatment in step S110 includes: the preset temperature is 70°C to 80°C, the stirring speed is 2000 r / min to 3000 r / min, and the time is 15 min to 30 min. The preset temperature is greater than the melting point Tm of the phase change substrate, enabling the phase change substrate to be fully melted, and combined with the stirring treatment, enabling the phase change substrate and the corrosion inhibitor to be fully emulsified and mixed evenly.
[0098] When the melting point Tm of the phase change substrate satisfies the conditional formula 20°C ≤ Tm ≤ 40°C, correspondingly, the preset temperature in the emulsification treatment is 50°C to 60°C, and the time is 1 h to 2 h; when the melting point Tm of the phase change substrate satisfies the conditional formula 40°C < Tm ≤ 60°C, correspondingly, the preset temperature in the emulsification treatment is 70°C to 80°C, and the time is 1 h to 2 h.
[0099] In some embodiments, both step S120 and step S130 can maintain the temperature at a preset temperature to maintain the molten state of the phase change substrate, and at this temperature, the nucleating agent of step S120 can be evenly dispersed, and the thickener of step S130 can also swell more fully, so that the obtained molten final mixture has a suitable viscosity, which is convenient for smooth filling into the heat storage space inside the metal heat storage shell.
[0100] In some embodiments, the first mixing treatment includes at least: a stirring speed of 80 r / min to 120 r / min for 1 h to 2 h, and an emulsification device is used to emulsify and shear the molten inorganic hydrated salt and the nucleating agent under the emulsification treatment conditions, so that the nucleating agent is evenly dispersed in the molten inorganic hydrated salt, so that the crystal phase integrity and dispersion uniformity of the crystals formed by the inorganic hydrated salt during the crystallization process are better.
[0101] In some embodiments, the second mixing process at least includes: adding the thickener to the mixture B in batches, stirring at a speed of 20 r / min to 40 r / min for 2 h to 3 h, and the weight of the thickener added each time is 20% to 25% of the total weight of the thickener. The thickener is added in small amounts and multiple times to facilitate the swelling of the thickener and to evenly disperse it in the inorganic hydrated salt phase change material, so as to better improve the phase separation and prevent the thickener from agglomerating and causing uneven dispersion when a large amount of thickener is added.
[0102] In some embodiments, when the phase change material combination does not include a thermally conductive filler, the thermally conductive filler can be added to the mixture B together with the thickener in step S130, and a second mixing process is performed to obtain a final mixture including the thermally conductive filler.
[0103] In some embodiments, when the particles of the nucleating agent and the thermal conductive filler are relatively large, the nucleating agent and the thermal conductive filler are pulverized separately and then mixed with other components. The particle size Dv of the pulverized nucleating agent is 50 Meet 200μm≤Dv 50 ≤400μm, the particle size Dv of the thermal conductive filler after crushing 50 Meet 300μm≤Dv 50 ≤900 μm, so that the nucleating agent can be evenly dispersed in the premixed liquid. The pulverization process can be carried out by at least one of a ball mill and a high-speed pulverizer.
[0104] The following is a method for preparing a phase change material in combination with an embodiment and a comparative example. Those skilled in the art will understand that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application. In the following examples, unless otherwise specified, all raw materials used are commercially available.
[0105] In each embodiment and comparative example of the present application, the performance testing method of the phase change material is as follows:
[0106] (1) Phase change temperature and supercooling test method
[0107] The phase change temperature is measured by the step cooling curve method: 100g of phase change material is placed in a high borosilicate glass bottle, a K-type thermocouple is inserted into the middle of the phase change material, and then the phase change material is heated to 20°C above the melting point of the phase change substrate and stabilized for 30 minutes. Then, it is placed in an environment 30°C below the melting point for natural cooling, and the temperature information of the phase change material changing with time is collected to obtain the temperature-time curve and the corresponding theoretical phase change temperature (T theory ) and the actual phase transition temperature (T actual ).
[0108] Theoretical phase transition temperature (T theory ) and the actual phase transition temperature (T actual ) is the supercooling degree (T sc ).
[0109] (2) Thermal enthalpy decay rate test method after 2000 cycles
[0110] The initial unit mass enthalpy of the phase change material is measured by DSC equipment.
[0111] The phase change material is loaded into the cycle test device and the melt-crystallization cycle is carried out according to the following steps:
[0112] (1) Initial temperature 0°C, let stand for 5 minutes;
[0113] (2) Perform heating treatment at a heating rate of 5°C / min, a stop temperature of 80°C, and stand for 5 min;
[0114] (3) Cooling treatment was performed at a cooling rate of 5°C / min, an end temperature of 0°C, and the mixture was allowed to stand for 1 min.
[0115] Among them, the above steps (1)-(3) are the first melt-crystallization cycle, and then the steps (2)-(3) are a melt-crystallization cycle. After the phase change material has been melt-crystallized for 2000 times, the unit mass thermal enthalpy of the phase change material after 2000 cycles is measured by DSC equipment.
[0116] The calculation formula of the thermal enthalpy decay rate per unit mass is: H% = (1-△H n / △H0)×100%;
[0117] Among them, △H n is the unit mass enthalpy of the phase change material after n cycles, kJ / kg;
[0118] △H0 is the initial unit mass enthalpy of the phase change material, kJ / kg.
[0119] (3) Energy storage density test method
[0120] The density of phase change materials was measured by density meter. s ) and liquid density (р l );
[0121] The solid-state specific heat capacity C of phase change materials was measured by differential scanning calorimetry (DSC) using the MDSC method. ps and liquid specific heat C pl .
[0122] The initial unit mass enthalpy ΔH0 of the phase change material was measured by differential scanning calorimetry (DSC).
[0123] The energy storage density △Q is calculated according to the following formula:
[0124] △Q=р s ×(T actual -10)×C ps +(р s +р l ) / 2×△H0+р l× (65-T actual )×C pl .
[0125] (4) Anticorrosion test method
[0126] Phase change materials are divided into organic phase change materials, inorganic phase change materials and eutectic phase change materials. Different material systems have different corrosion characteristics to metals. To ensure the authenticity of the test, the parts in the system that will directly or indirectly contact the phase change material will be used to evaluate its service life, and two test methods are used to examine the corrosion characteristics of the phase change material to metals.
[0127] The components were buried in phase change materials and placed in a constant temperature box with a temperature 15°C higher than the phase change temperature of the phase change material for a thermal environment corrosion experiment. The time period was 209 days (5000 hours), and sampling was carried out every 42 days (1000 hours). The micromorphology of the corroded samples was analyzed by scanning electron microscopy, the main components of the corrosion products were analyzed by elemental analysis and EDX, and the corrosion depth of the samples was observed using a 3D microscope.
[0128] Example 1-1
[0129] This embodiment provides a method for preparing a phase change material made from a phase change material, the method comprising the following steps:
[0130] (1) Emulsification treatment
[0131] Weigh 85.0 g of inorganic phase change substrate sodium acetate trihydrate (CH3COONa·3H2O) and 1.0 g of corrosion inhibitor BTA, heat to a preheating temperature of 75°C in an emulsifying device, perform emulsification treatment, and stir at a speed of 2500 r / min for 20 min to obtain a molten mixture A.
[0132] Based on the total weight of the phase change material, the weight percentage of sodium acetate trihydrate is 85.0 wt.%, and the weight percentage of BTA is 1.0 wt.%.
[0133] (2) First mixing process
[0134] At 75° C., 3.0 g of nucleating agent disodium hydrogen phosphate dodecahydrate and 7.0 g of thermally conductive filler carbon nanotubes were added to the molten mixture A, and the first mixing treatment was carried out in a stirring device at a stirring speed of 90 r / min for 1.5 h to obtain a mixture B.
[0135] Wherein, based on the total weight of the inorganic hydrated phase change material, the weight percentage of disodium hydrogen phosphate dodecahydrate is 3.0 wt.%, and the weight percentage of the carbon nanotubes is 7.0 wt.%.
[0136] (3) Second mixing process
[0137] At 75° C., add sodium carboxymethyl cellulose, a thickener, to the final mixture in 5 portions, and perform a second mixing treatment in a stirring device at a stirring speed of 30 r / min for 2 h. Each addition amount is 0.6 g to obtain a molten final mixture.
[0138] Wherein, based on the total weight of the inorganic hydrated phase change material, the weight percentage of sodium carboxymethyl cellulose is 4.0 wt.%.
[0139] (4) Cooling treatment
[0140] The molten final mixture is cooled to room temperature 25°C, and the final mixture solidifies to form a phase change material.
[0141] The phase change layer of the heat storage unit is formed by cooling the molten final mixture to room temperature 25°C and solidifying it.
[0142] Examples 1-2 to 1-7, Examples 1-13 to 1-21, and Comparative Examples 1-1 to 1-4 are the same as Example 1-1, except that the contents of the phase change substrate, nucleating agent, corrosion inhibitor, thickener and thermal conductive filler are adjusted as shown in Table 1 in each processing step.
[0143] Example 1-8 is the same as Example 1-6 except that the type of phase change substrate is adjusted as shown in Table 1 in step (1) and the processing temperature is adjusted to 50° C. in steps (1) to (2) as shown in Table 1.
[0144] Example 1-9 is the same as Example 1-6 except that the type of phase change substrate is adjusted as shown in Table 1 in step (1) and the processing temperature is adjusted to 50° C. in steps (1) to (2) as shown in Table 1.
[0145] Example 1-10 is the same as Example 1-6 except that the type of phase change substrate is adjusted as shown in Table 1 in step (1) and the processing temperature is adjusted to 70° C. in steps (1) to (2) as shown in Table 1.
[0146] Example 1-11 is the same as Example 1-6 except that the type of phase change substrate is adjusted as shown in Table 1 in step (1) and the processing temperature is adjusted to 50° C. in steps (1) to (2) as shown in Table 1.
[0147] Example 1-12 is the same as Example 1-6 except that the type of phase change substrate is adjusted as shown in Table 1 in step (1) and the processing temperature is adjusted to 70° C. in steps (1) to (2) as shown in Table 1.
[0148] The preparation parameters and performance parameters of Examples 1-1 to 1-21 and Comparative Examples 1-1 to 1-4 are shown in Table 1.
[0149]
[0150] It can be seen from Examples 1-1 to 1-24 and Comparative Examples 1-1 to 1-4 in Table 1 that when a saturated fatty acid, an alcohol compound or an inorganic phase change substrate is selected as the phase change substrate, and it is used in combination with a corrosion inhibitor in the phase change material, the phase change temperature, the enthalpy value after 2000 cycles, the enthalpy value decay rate after 2000 cycles, the supercooling degree and the energy storage density of 10°C to 65°C of the obtained phase change material are all within a suitable range, and the phase change material of the embodiment of the present application can be used in a heat pump system to store cold and heat. Among them, when the weight percentage of the phase change substrate is less than 85wt.%, the effects of the enthalpy value energy storage density of the phase change material are poor. When the weight percentage of the phase change substrate is higher than 95wt.%, the content of the phase change substrate is too high, which easily leads to insufficient content of other components of the phase change material, and the problem of phase separation is prone to occur. When the weight percentage of the corrosion inhibitor is lower than the lower limit of 0.5wt.%, due to the low content of the corrosion inhibitor, the coverage and thickness of the surface complex formed are insufficient, and the metal protection effect is poor. When the weight percentage of the corrosion inhibitor is higher than the upper limit of 1.5wt.%, it will cause redundancy of corrosion inhibitor, resulting in waste of costs and aggravating the environmental burden.
[0151] like Figure 3a As shown, the phase change material prepared in Example 1-6 is used as a phase change layer in contact with a copper heat exchange tube. The outer surface morphology of the copper heat exchange tube at the joint after the corrosion test for 1000 hours in a 75°C environment; Figure 3b As shown, the phase change material prepared in Comparative Example 1-1 is used as a phase change layer in contact with a copper heat exchange tube. The morphology of the outer surface of the copper heat exchange tube after the corrosion test lasted for 1000 hours in a 75°C environment. Figure 3a It can be seen that the outer surface morphology of the copper heat exchange tube joint is good, and there is no large area of corrosion. Figure 3b It can be seen that a large area of corrosion occurs on the outer surface of the joint of the copper heat exchange tube, indicating that the phase change material of the embodiment of the present application has a small degree of corrosion on the joint of the copper heat exchange tube and has a good anti-corrosion effect.
[0152] Figure 4 The figure shows the corrosion depth of the copper heat exchange tube after the phase change material prepared in Examples 1-6 is used as the phase change layer in contact with the copper heat exchange tube in a 75°C environment after 1000 hours of corrosion experiment. Figure 4 It can be seen that after 1000h of high temperature corrosion test, the corrosion depth of the copper tube is less than 20μm.
[0153] like Figure 5 As shown, the phase change material prepared in Example 1-6 is used as a phase change layer in contact with 304 stainless steel. The corrosion test lasts for 1000 hours in a 75°C environment. Figure 5 It can be seen that the surface of the 304 stainless steel sheet is intact and there is no uniform corrosion.
[0154] like Figure 6 The figure shows the corrosion diagram of the aluminum sheet in which the phase change material prepared in Comparative Example 1-1 is used as a phase change layer in contact with an aluminum sheet and corroded for 1000 hours in a 75°C environment. Figure 6 It can be seen that the area of corrosion formed on the surface of the aluminum sheet (the green area is the corroded area of the aluminum sheet) accounts for about 3 / 4 of the area of the aluminum sheet, and the degree of corrosion is relatively serious.
[0155] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A heat storage unit, characterized in that: Used in a heat pump system, the heat storage unit comprises a metal heat storage shell and a phase change layer, the metal heat storage shell has a heat storage space inside, and the phase change layer is filled in the heat storage space; Wherein, the phase change layer comprises a phase change material, and the phase change material comprises the following components: Phase change substrate 85.0wt.%~95.0wt.%, nucleating agent 1.0wt.%~3.0wt.%, thickener 2.0wt.%~4.0wt.%, corrosion inhibitor 0.5wt.%~2.0wt.%; The phase change substrate includes one of saturated fatty acids, alcohol compounds or inorganic phase change substrates; The nucleating agent is selected from at least one of phosphates, silicates, and carbonates; The corrosion inhibitor includes at least one of nitrogen-containing heterocyclic compounds, oxygen-containing heterocyclic compounds, molybdates, chromates and tungstates.
2. The thermal storage unit according to claim 1, characterized in that: Based on the total weight of the phase change material, the phase change material includes the following components: Phase change substrate 92wt.%~94wt.%, nucleating agent 2.0wt.%~3.0wt.%, thickener 3.0wt.%~4.0wt.%, corrosion inhibitor 0.5wt.%~1.5wt.%.
3. The thermal storage unit according to any one of claims 1 to 2, characterized in that: The weight ratio of the phase change substrate to the corrosion inhibitor ranges from 90.5 to 92.
5.
4. The thermal storage unit according to claim 1, characterized in that: The saturated fatty acid of the phase change substrate is selected from at least one of myristic acid, palmitic acid, and fatty acid; The alcohol compound of the phase change substrate is selected from at least one of mannitol, polyethylene glycol, and dodecanol; The inorganic phase change substrate of the phase change substrate is selected from at least one of sodium sulfate decahydrate, calcium chloride hexahydrate, sodium acetate trihydrate, magnesium chloride hexahydrate, sodium carbonate decahydrate, and sodium thiosulfate pentahydrate.
5. The thermal storage unit according to claim 1, characterized in that: The nitrogen-containing heterocyclic compound of the corrosion inhibitor is at least one selected from carboxyethyl imidazoline and its derivatives, benzotriazole and its derivatives, and imidazoline; The oxygen-containing heterocyclic compound of the corrosion inhibitor is selected from at least one of chitosan-o-vanillin Schiff base, furfural-adenine Schiff base, and furfural-melamine Schiff base; The molybdate of the corrosion inhibitor is selected from at least one of sodium molybdate, strontium molybdate and nickel molybdate; The chromate of the corrosion inhibitor is selected from at least one of sodium chromate, potassium chromate and magnesium chromate; The tungstate of the corrosion inhibitor is selected from at least one of calcium tungstate, sodium tungstate, cobalt tungstate and ferrous tungstate.
6. The thermal storage unit according to claim 1, characterized in that: The thickener is selected from at least one of hydroxymethyl cellulose, soluble starch, gelatin, polyvinyl pyrrolidone, sodium polyacrylate and xanthan gum.
7. The thermal storage unit according to claim 1, characterized in that: The metal heat storage housing comprises: main housing; A plurality of heat-conducting fins are arranged in the inner space of the main housing, each of the heat-conducting fins having a heat-conducting hole; A heat exchange tube is arranged in the inner space of the main shell and is provided with a plurality of heat conduction holes of the heat conduction fins. The main shell, the plurality of heat conduction fins and the heat exchange tube define the heat storage space; The phase change layer is filled in the heat storage space and is in contact with the outer surface of the heat exchange tube and the outer surface of the heat conductive fin to exchange heat with the heat exchange medium in the heat exchange tube; A material of at least one of the main housing, the heat conducting fins, and the heat exchange tubes includes copper.
8. A method for assembling a heat storage unit, characterized in that: include: After mixing the components of the phase change material according to any one of claims 1 to 7, a final mixture is obtained, and the final mixture is filled into the heat storage space of the metal heat storage shell, and the final mixture forms the phase change layer.
9. The assembly method according to claim 8, characterized in that: Mixing the components of the phase change material comprises the following steps: The phase change substrate and the corrosion inhibitor are mixed and heated to a preset temperature for emulsification treatment, wherein the preset temperature is greater than the melting point of the phase change substrate to obtain a molten mixture A; Mixing the molten mixture A with the nucleating agent to perform a first mixing process to obtain a mixture B; Mixing the mixture B with the thickener, and performing a second mixing process to obtain the molten final mixture; Filling the heat storage space of the metal heat storage shell with the final mixture includes: filling the heat storage space inside the metal heat storage shell with the molten final mixture, and the molten final mixture is cooled and solidified to form the phase change layer.
10. The assembly method according to claim 9, characterized in that: The emulsification treatment at least includes: the preset temperature is 70° C. to 80° C., the stirring speed is 2000 r / min to 3000 r / min, and the time is 15 min to 30 min. The first mixing process at least includes: a stirring speed of 80 r / min to 120 r / min and a time of 1 h to 2 h; The second mixing process at least includes: adding the thickener to the mixture B in batches, with a stirring speed of 20r / min to 40r / min for 2h to 3h, and the weight of the thickener added each time is 20% to 25% of the total weight of the thickener.
11. A heat pump system, characterized in that: include: A heat source, used to provide heat; and As in any one of claims 1 to 7 above, the phase change material of the heat storage unit is used to obtain heat provided by the heat source to perform phase change energy storage.
Citation Information
Cited By
Thermal storage unit and assembly method therefor, and heat pump system
WO2026067178A1
